Vaginal Exposure to Candida albicans During Early Gestation Results in Adverse Pregnancy Outcomes via Inhibiting Placental Development - Dong, Zhiyong; Fan, Chong; Hou, Wenwen; Rui, Can; Wang, Xinyan; Fan, Yuru; Zhao, Ling; Wang, Qing; Wang, Zhichong; Zeng, Xin; Feng, Shanwu; Li, Ping (Frontiers in Microbiology, 2022)
Vulvovaginal candidiasis (VVC) is considered the second most common cause of vaginitis after bacterial vaginosis and the most common lower genital tract infection during pregnancy. Candida albicans (C. albicans), an opportunistic pathogen, is the major species causing VVC. Recently, increasing researches have shown that lower reproductive tract infection during pregnancy can lead to various adverse pregnancy outcomes. However, the underlying mechanisms are not fully understood. Hence, we successfully established a mouse model of vaginal C. albicans infection and characterized the adverse pregnancy outcomes. C. albicans infection strikingly increased abortion rate and decreased litter size. Further analysis of placental development demonstrated that placental structure was abnormal, including that the area of spongiotrophoblast (Spo) and labyrinth (Lab) was reduced, and the formation of placental vessel was decreased in Lab zone. Accordingly, the expression of marker genes during placental development was down-regulated. Collectively, the above findings revealed that vaginal C. albicans infection during pregnancy can inhibit placental development and ultimately lead to adverse pregnancy outcomes. This study enhances our comprehension of the effect of VVC on pregnancy, and placental dysplasia as a feasible orientation to explore VVC during pregnancy.